The Effect Of Motivation, Organizational Commitment And Job Satisfaction Towards Organizational Citizenship Bahavior (OCB) at Headquarters of The Entrepreneurship Training Agency, Dili-Timor-Leste - Maria Cárceres Pinto Soares; I Gede Riana; Augusto da Conceição Soares (LPPM Institut Teknologi dan Sains Mandala, 2020)
This study aims to determine: (1) The influence of motivation on the Organizational Citizenship Behavior of employees of the Entrepreneurship Training Agency, Dili, Timor-Leste. (2) The Effect of Organizational Commitment on Organizational Citizenship Behavior of Employees of the Entrepreneurship Training Agency, Dili Timor-Leste. (3) The Effect of Job Satisfaction on Organizational Citizenship Behavior of Employees of the Entrepreneurship Training Agency, Dili, Timor-Leste. The population in this study amounted to 33 employees who work at the Head Office of the Entrepreneurship Training Agency, Dili, Timor-Leste by determining the saturated sample of the sample with the highest to lowest respondent rates. The findings of this study are to obtain the highest average value is 42.4%. Then the lowest value obtained a value of 0.001%. Keywords: Motivation, Organizational Commitment, Job Satisfaction, and Organizational Citizenship Behavior (OCB).